"Who is Buddha? I am Buddha."—The motivations and experiences of Chinese young adults attending a Zen meditation camp in Taiwan. Issue 4 (7th August 2020) - Song, Yang; Yan, Libo
Abstract: Religious tourism is not limited to believers, and those without a religious belief could also be interested in religious sites and participate in various forms of religious activities and events. Previous studies have explored the motivations and experiences of religious and nonreligious tourists. However, the spirituality-seeking of nonreligious people participating in religious tourism events remains under-investigated. This study employed a Zen meditation camp in Taiwan as a case of a religious tourism event, and examined why Chinese young adults without a religious belief participate in the meditation camp and what experiences they obtain from participation in such an event. Analyses of data collected from formal interviews revealed three types of motivations: self-motivated, pushed by family members, and to be with friends. This study also found three types of inner experience of the mediation camp participants: feelings, enlightenment or transformation, and sensory awareness. Theoretical and practical implications and future research directions are also discussed.